2013
DOI: 10.1148/radiol.13122234
|View full text |Cite
|
Sign up to set email alerts
|

Human Renovascular Disease: Estimating Fractional Tissue Hypoxia to Analyze Blood Oxygen Level–dependent MR

Abstract: Purpose:To test the hypothesis that fractional kidney hypoxia, measured by using blood oxygen level-dependent (BOLD) magnetic resonance (MR) imaging, correlates with renal blood flow (RBF), tissue perfusion, and glomerular filtration rate (GFR) in patients with atherosclerotic renal artery stenosis (RAS) better than regionally selected region of interest-based methods. Materials and Methods:The study was approved by the institutional review board according to a HIPAA-compliant protocol, with written informed c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 29 publications
0
56
0
Order By: Relevance
“…The severity of the artifact increases at higher magnetic fields, and warrants careful selection of regions of interest. Notably, analytical methods utilizing histogram-based tools that recognize the variability of the BOLD signal intensity within the regions of interest may be capable of detecting differences (40) and introduce new markers beyond the traditional mean of R 2 * value, such as their distribution (41,42).…”
Section: Blood Oxygen Level-dependent Mrimentioning
confidence: 99%
“…The severity of the artifact increases at higher magnetic fields, and warrants careful selection of regions of interest. Notably, analytical methods utilizing histogram-based tools that recognize the variability of the BOLD signal intensity within the regions of interest may be capable of detecting differences (40) and introduce new markers beyond the traditional mean of R 2 * value, such as their distribution (41,42).…”
Section: Blood Oxygen Level-dependent Mrimentioning
confidence: 99%
“…Two ROIs were traced: one that selected the renal cortex (large segment) for estimation of cortical R2*, and the second, which included the entire kidney slice, including both cortex and medulla while excluding the renal collecting system and any incidental renal cysts to determine the fractional tissue hypoxia of the entire slice, as previously described [5].…”
Section: Mri Data Analysismentioning
confidence: 99%
“…that reflect local levels of deoxyhemoglobin within the kidney [5,[22][23][24]. We have previously shown that R2* levels are higher in stenotic kidneys compared with contralateral kidneys in ARAS and kidneys of hypertensive patients [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…39 miR-26a level was evaluated using RT-PCR in renal vein and inferior vena cava samples in patients with RVD or EH and peripheral venous samples from healthy volunteers. Total RNAwas isolated from 400-ml plasma samples by the mirVana PARIS Total RNA Isolation Kit (Life Technologies, Carlsbad, CA).…”
Section: Procedures In Humansmentioning
confidence: 99%